Surface Electromyography Thresholds as a Measure for Performance Fatigability During Incremental Cycling in Patients With Neuromuscular Disorders - Voet, Nicoline B. M.; Saris, Christiaan G. J.; Thijssen, Dick H. J.; Bastiaans, Vincent; Sluijs, David E.; Janssen, Mariska M. H. P. (Frontiers in Physiology, 2022)
Valid measures for performance fatigability could help people with neuromuscular disorders (NMD) find the right intensity of daily life activities and exercise. The primary aim of this study was to determine the relative timing of both surface electromyography thresholds (sEMG Ths) and ventilatory thresholds (VTs) in patients with NMD as compared with healthy controls (HC) during a maximal ergospirometry cycling test. We hypothesized that in patients with NMD, the sEMG Ths would occur relatively earlier in time than the VTs, compared to HC, because relatively more performance fatigability occurs. In total, 24 HC and 32 patients with a NMD performed a cardiopulmonary exercise test (CPET) on a bicycle using a 10-minute ramp protocol, during which we collected ergospirometry data (power (W) at the first VT (VT1) and the second VT (VT2) and sEMG data of lower leg muscles (power at the first sEMG threshold (sEMG Th1) and the second sEMG threshold (sEMG Th2)). Threshold determination was feasible for VT1,VT2, and sEMG Th2 (>80%), while the feasibility of sEMG Th1 was low (<43%). Inter-rater reliability of sEMG Th1 varied between muscles (ICC between 0.169 and 0.990), while inter-rater reliability of sEMG Th2 was high for all muscles (ICC>0.95). Test-retest reliability was excellent in all participants for VT1, VT2, and sEMG Th2 (ICC>0.9). In line with our hypothesis, the sEMG Ths of patients occurred at relatively lower power values than HC. At the same time, for the normalized VTs, only VT1 showed a significant difference between HC and patients. In line with our hypothesis, normalized values for sEMG Ths and VTs were lower for NMD patients than the HC. The EMG Ths' reliability was higher than the VTs; however, the feasibility was lower. As expected, the sEMG Ths, particularly the sEMG Th1, occurred relatively earlier than VT1 in NMD patients, as compared with HC. A possible explanation could be (a combination of) a difference in fiber type composition, disuse, and limited muscle-specific force in patients with NMD. To generalize the measurements to daily life activities for future use in prescribing and evaluating rehabilitation interventions, sEMG measurements during submaximal dynamic exercises are needed.